Kinetics of sodium borohydride hydrolysis in aqueous-basic solutions - Retnamma, Rajasree (2013)
Liquid-phase catalytic hydrolysis of sodium borohydride (NaBH4) for hydrogen production necessitates long-term stability of base-stabilized NaBH4 solutions at higher temperatures. The present paper reports the kinetics of aqueous-basic solutions containing 20 wt% NaBH4 with 1-15 wt% sodium hydroxide (NaOH) at 80 0C. The established kinetic model employs a modified isoconversional method assuming single-step kinetics. The estimation of kinetic parameters is performed by gPROMS (general PRocess Modeling System) parameter estimation tool. The reaction kinetics differs from low to highly-concentrated NaOH solutions. In highly-basic (.10 wt% NaOH), aqueous solutions of NaBH4, the rate is independent of NaOH concentration, while for lower-basic (< 10 wt% NaOH) solutions, the dependence is -0.57, confirming the inhibition of hydrolysis kinetics by NaOH.